Evaluation model of teaching effectiveness of sports characteristic course based on intelligent fuzzy system - Chen, Hanying (Journal of computational methods in sciences and engineering, 2022)
In order to improve the accuracy of the teaching effect evaluation, a teaching effect evaluation model based on the intelligent fuzzy system is designed. The evaluation index are selected based on the teaching situation of physical education courses, relevant national policy documents, subject textbooks, intelligent fuzzy system to modify the index system through expert interview, determine the weight coefficient of each index by hierarchical analysis method (AHP), and calculate the single layer and total ranking of the index matrix to realize the evaluation of physical education courses. The test results show that the fuzzy evaluation accuracy of the proposed model is above 95.63%, with high evaluation performance and strong utility.